2013
DOI: 10.1002/anie.201304273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Site‐Specific Functionalization of Tetravalent, Hexavalent, and Dodecavalent Silica Particles

Abstract: Different shapes: Tetravalent, hexavalent, and dodecavalent silica particles were obtained by the growth of the silica core of binary tetrapods, hexapods, and dodecapods, respectively. The surface of the multivalent particles can be regioselectively functionalized, thereby leading to particles with anisotropic geometry and chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 33 publications
0
66
0
Order By: Relevance
“…Paula et al found that the formation of MSNs with center‐radial large pore size (Table , line 18) may be induced by hydrophobic groups during hydrolysis and co‐condensation of phenyltriethoxysilane and TEOS, and their self‐assembly process with CTAB. Ravaine's group developed a high‐yield chemical route for the preparation of tetra‐, hexa‐, and dodecavalent silica particles via the limited growth of the silica core using the corresponding binary polystyrene (PS)/silica multipods (tetra‐, hexa‐ or dodeca‐pods) as special hard templates, and these special hard templates can be controllably synthesized by a seeded‐growth emulsion method ( Figure ). Wiesner reported a one‐pot synthesis approach for novel multicompartment MSNs containing a core with a cage‐like cubic mesopore phase and up to four branches with hexagonally packed cylindrical mesopore phase, which epitaxially grow out of the cubic core vertices.…”
Section: Synthesis Methods Of Dendritic Silica Particles With Center‐mentioning
confidence: 99%
See 1 more Smart Citation
“…Paula et al found that the formation of MSNs with center‐radial large pore size (Table , line 18) may be induced by hydrophobic groups during hydrolysis and co‐condensation of phenyltriethoxysilane and TEOS, and their self‐assembly process with CTAB. Ravaine's group developed a high‐yield chemical route for the preparation of tetra‐, hexa‐, and dodecavalent silica particles via the limited growth of the silica core using the corresponding binary polystyrene (PS)/silica multipods (tetra‐, hexa‐ or dodeca‐pods) as special hard templates, and these special hard templates can be controllably synthesized by a seeded‐growth emulsion method ( Figure ). Wiesner reported a one‐pot synthesis approach for novel multicompartment MSNs containing a core with a cage‐like cubic mesopore phase and up to four branches with hexagonally packed cylindrical mesopore phase, which epitaxially grow out of the cubic core vertices.…”
Section: Synthesis Methods Of Dendritic Silica Particles With Center‐mentioning
confidence: 99%
“…And the corresponding TEM images of tetravalent, hexavalent, and dodecavalent silica particles. Reproduced with permission . Copyright 2013, Wiley.…”
Section: Synthesis Methods Of Dendritic Silica Particles With Center‐mentioning
confidence: 99%
“…Zuschriften from highly symmetrical silica/polystyrene (PS) multipods following our already reported procedure, [17] and the initial morphological purity of the sp-, sp 2 and sp 3 -like CAs was 86 %, 69 %a nd 76 %, respectively.T he successful amination of the PS chains remaining within the dimples was checked by z potential measurements and the site-specific tagging with citrate-stabilized gold nanoparticles ( Figure S2). We first investigated the assembly of the sp 3 -like CAs with 100 nm silica nanospheres in a4( in terms of the number of cavities)/4 stoichiometric ratio.F igure 1a shows AX 4 -type CMs,t he colloidal analogues of molecules such as tetrabromomethane (CBr 4 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Colloidal MSNs with ultralarge dimples can be prepared by removing the polystyrene nanoparticles selectively. 313,333 3.4.1.3 Use of Emulsions; Recently, emulsions stabilized by surfactants have been used as templates of MSNs. Although emulsions can be prepared easily by mixing oil and water, such simple emulsions cannot be utilized as templates of mesopores.…”
Section: Soft Template;mentioning
confidence: 99%